Methods And Approaches Adopted In Teaching English And Learning Outcome In Lower Primary Vernacular Schools With Special Reference To Dhemaji District In Assam - Hari Prasad Kaphley (Elementary Education Online, 2017)
In the present age of post globalization era with advanced technology at work in almost every sphere of human life, there is no denying of the importance of English as language of - information technology, language of social intercourse both at national as well as international level, language of higher studies especially in technical and professional education and as a language of job opportunity. Nevertheless, majority of students of vernacular medium schools are found to possess poor knowledge of English as language for communication and their academic performance in English as a course in curriculum is dismaying. This dismal state of affair continues to persist right from lower primary schools to even at college level. Being a foreign language obviously we don’t have spontaneous learning exposure as in the case of mother tongue acquisition. Many a research studies have been made on methods of teaching-learning of English. Varied innovative techniques and approaches have been evolved and employed in classroom teaching now a day. Language learning is a process of learning four language skills viz-listening, speaking, reading and writing. Effectiveness of teaching English largely depends on teachers’ proficiency and efficiency in English and their knowledge of the varied methods and techniques of teaching English and also their endeavour and dedication. Role of English teachers in classroom situation is crucial in teaching English because students do not have opportunity for social exposure to English except classroom teaching and text books. The present paper attempts to highlight the methods and techniques used in teaching English at lower primary vernacular schools as well as students’ performance in English based on the case study made in the district of Dhemaji.